Appraisal of potential environmental risks associated with human antibiotic consumption in Turkey - Turkdogan, F. Ilter; Yetilmezsoy, Kaan (ELSEVIER SCIENCE BV, 2009)
A comprehensive analysis of Turkish antibiotic data was conducted to evaluate potential environmental risks associated with antibiotic consumption in Turkey for year 2007. Antibiotics were defined for systemic use or group J01 of the WHO Anatomical Therapeutic Chemical (ATC) classification system. Total emissions and prescriptions for each ATC group were classified separately into 17 different J01 categories and three forms of medication (capsule/tablets, injectables and suspensions). Capsules and tablets were found as the most emitted form of medication in year 2007, with a total emission rate of about 585.5 tons/year (76%). Total antibiotic emission rates including all forms of medications were determined to be about 664.2 tons/year (86%) and 110.1 tons/year (14%) for adult and pediatric patients, respectively. An environmental risk assessment of 8 human antibiotics was conducted according to the EU draft guidance (CEC/III/5504/94, draft 6, version 4) and the risk was indicated by the ratio of predicted environmental concentration (PEC) to predicted no effect concentration (PNEC) for the aquatic environment. Available acute and chronic toxicity data were collected from the open peer-reviewed literature to derive PNEC. Risk quotients (PEC/PNEC) were then calculated for 8 pharmaceutical substances. PEC/PNEC ratio exceeded 1.0 for beta-lactams (cephalosporins and penicillins), fluoroquinolones, macrolides and aminoglycosides. The findings of this study concluded that the release of these compounds from wastewater treatment plants may potentially be of an important environmental concern based on today's use of antibiotics in Turkey. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Antibiotic; Medication; Environmental risk; Risk assessment; Wastewater treatment plant; PHARMACEUTICAL WASTE-WATER; SOLID-PHASE EXTRACTION; BACTERIUM VIBRIO-FISCHERI; TANDEM MASS-SPECTROMETRY; TRACE DETERMINATION; LACTAM ANTIBIOTICS; ALGAL TOXICITY; REMOVAL; TRIMETHOPRIM; SULFONAMIDE; Engineering; Environmental Sciences & Ecology